Introduction to Web Matrix: ASP. NET Development for Beginners - Hardy, Colin; Stobart, Simon (Elsevier Science & Technology, 2003)
An Introduction to Web Matrix provides an easy to follow treatment of the application of this new software, which is rapidly becoming the preferred vehicle for the teaching of website design.